The Moderating Effect of Market Power on Financial Policies, Cash Conversion Cycle, and Debt Capital Toward Firm Value in Cyclical Industries - Oppie Junia Purnamasari Oppie; Fajar Nur Cholis Fajar; Henny Setyo Lestari; Farah Margaretha (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the effect of working capital investment policy, working capital financing policy, cash conversion cycle (“CCC”), and debt capital on firm value, as well as to analyze the moderating role of market power in these relationships. The research focuses on non-financial companies operating in cyclical industries listed on the Indonesia Stock Exchange (“IDX”) during the period 2020–2024. Using a quantitative approach, the study employs panel data regression analysis with a total sample of 40 firms observed over five years, resulting in 200 firm-year observations. Firm value is proxied by Tobin’s Q, while market power is proxied by the firm’s market share, measured as the ratio of firm sales to total sales of all firms in the sample. The empirical analysis is conducted using EViews software with fixed effect and random effect model selection procedures. This research contributes to the financial management literature by integrating working capital policies, debt capital, and market power within a comprehensive framework, particularly in the context of emerging markets and cyclical industries.